Surface Modification of SnO2 with Phosphonic Acids - Ramona Gheonea; Carmen Mak; Eleonora Cornelia Crasmareanu; Vasile Simulescu; Nicoleta Plesu; Gheorghe Ilia (Journal of Chemistry)
The aim of the present work was the study of phosphonic acids grafting on the surface of SnO2 at different molar ratios. In this paper we describe the functionalization of SnO2 surfaces with phosphonic acids RPO(OH)2. The surface modification process was achieved by using phenyl-phosphonic acid (PPA) and vinyl-phosphonic acid (VPA). The synthesized materials were investigated by using FT-IR, TGA (in air and in nitrogen), EDX, ESEM, and TEM methods. This synthetic approach has many advantages: films with optical quality and controlled thickness can be obtained using low temperatures and cheap raw materials, by using “green chemistry” synthetic routes. The hybrid materials have structures diversity and fascinating applications, attracting attention for a long time, due to their potential.